PEMAHAMAN ORANG TUA TENTANG KEMATIAN ORANG PERCAYA BERDASARKAN 2 KORINTUS 5:1–10 - Ruata, Jayson (STT INDONESIA MANADO, 2020)
Death is something that cannot be avoided by all living creatures and even humans. The meaning of the word